2007
DOI: 10.1007/s00198-007-0465-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different doses and time intervals of oral vitamin D supplementation with or without calcium in elderly nursing home residents

Abstract: Summary The effect of equivalent oral doses of vitamin D3 600 IU/day, 4200 IU/week and 18,000 IU/month on vitamin D status was compared in a randomized clinical trial in nursing home residents. A daily dose was more effective than a weekly dose, and a monthly dose was the least effective. Introduction It is assumed that equivalent daily, weekly or monthly doses of vitamin D3 equally influence vitamin D status. This was investigated in a randomized clinical trial in nursing home residents. Methods The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 30 publications
9
112
2
1
Order By: Relevance
“…The increase in serum 25OHD was about 1.3 ng/100 IU, in line with most previous studies in subjects with a similarly low baseline vitamin D status. The results confirm a previous (equally small) study in elderly subjects (mean age of 80 years [9]), whereas others found a slightly lower efficacy of monthly compared to daily or weekly doses [10]. Collectively, however, these reports confirm that these strategies yield essentially similar results especially when taking into account the wide interindividual differences.…”
supporting
confidence: 80%
“…The increase in serum 25OHD was about 1.3 ng/100 IU, in line with most previous studies in subjects with a similarly low baseline vitamin D status. The results confirm a previous (equally small) study in elderly subjects (mean age of 80 years [9]), whereas others found a slightly lower efficacy of monthly compared to daily or weekly doses [10]. Collectively, however, these reports confirm that these strategies yield essentially similar results especially when taking into account the wide interindividual differences.…”
supporting
confidence: 80%
“…Some studies evaluated the efficacy of high doses at monthly or 3-month intervals, but most studies have used the officially recommended cholecalciferol dose of 600-800 IU/day, or equivalents thereof (12)(13)(14)(15)(16). Most studies used predefined fixed doses, irrespective of the degree of vitamin D deficiency and body weight, and assessed the efficacy of the regimen after 4-6 months or longer.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for that would be the short duration of the intervention. Chel et al (25) studied the effects of daily supplementation with 600 IU vitamin D3 for 4 mo in elderly nursing home residents. The serum 25OH-D level increased from 9.2 to 28.0 ng/mL, and the percentage of subjects with serum 25OH-D below 20 ng/mL was only 10.9%.…”
Section: Discussionmentioning
confidence: 99%